The Linguocultural Concept of Pechal’/Pechal’nyy in Alexander Herzen’s My Past and Thoughts - Gerkerova, Aleksandra; Davidovitch, Nitza (Journal of Education Culture and Society, 2026)
Aim. This study analyses the linguocultural concept pechal’/pechal’nyy (sadness/sad) in Alexander Herzen’s My Past and Thoughts, exploring its linguistic and cultural functions. It examines how pechal’ serves as a marker of emotional, intellectual, and moral depth, revealing layers of meaning in the portrayal of characters, their worldview, and 19th-century Russian mentality. Methods. The study uses quantitative and qualitative methods, including content and contextual analysis. It identifies and categorises all occurrences of pechal’ and pechal’nyy, examining their frequency, semantic roles, emotional connotations, and cultural-historical associations. It also draws on dictionary definitions, gender and referent classification, and analyses of how pechal’ is used in depicting Herzen’s circle. Results. Pechal’ appears 188 times and functions as a culturally charged emotional concept denoting sorrow, reflection, and existential awareness. It is closely linked to characters with intellectual depth, critical thought, and emotional sensitivity. The analysis shows that pechal’ is not only a personal emotion but also a cultural phenomenon embedded in Russian identity and literary tradition. It also marks Herzen’s inner circle, distinguishing genuine suffering from theatrical melancholy. Conclusions. The study identifies pechal’ as a linguocultural marker uniting emotion, intellect, and moral reflection. It functions as a culturally shaped emotional-cognitive response to the world’s imperfections, marking individuals of ethical sensitivity. Traced across characters and contexts, pechal’ serves as both a literary device and a cultural code, illustrating how emotional lexemes convey complex ideological and identity meanings in historical and literary discourse.